RecQ4 Facilitates UV Light-induced DNA Damage Repair through Interaction with Nucleotide Excision Repair Factor Xeroderma Pigmentosum Group A (XPA) - Fan, Wei; Luo, Jianyuan (The Journal of biological chemistry, 2008)
Mutations in the RECQL4 helicase gene have been linked to Rothmund-Thomson syndrome, which is characterized by genome instability, cancer susceptibility, and premature aging. To better define the cellular function of the RecQ4 protein, we investigated the subcellular localization of RecQ4 upon treatment of cells with different DNA-damaging agents including UV irradiation, 4-nitroquinoline 1-oxide, camptothecin, etoposide, hydroxyurea, and H2O2. We found that RecQ4 formed discrete nuclear foci specifically in response to UV irradiation and 4-nitroquinoline 1-oxide. We demonstrated that functional RecQ4 was required for the efficient removal of UV lesions and could rescue UV sensitivity of RecQ4-deficient Rothmund-Thomson syndrome cells. Furthermore, UV treatment also resulted in the colocalization of the nuclear foci formed with RecQ4 and xeroderma pigmentosum group A in human cells. Consistently, RecQ4 could directly interact with xeroderma pigmentosum group A, and this interaction was stimulated by UV irradiation. By fractionating whole cell extracts into cytoplasmic, soluble nuclear, and chromatin-bound fractions, we observed that RecQ4 protein bound more tightly to chromatin upon UV irradiation. Taken together, our findings suggest a role of RecQ4 in the repair of UV-induced DNA damages in human cells.